KARAKTERISTIK MI BASAH JAGUNG AKIBAT PENGARUH LAJU PENGUMPANAN DAN PENAMBAHAN GUAR GUM [Characteristics of Wet Corn Noodle: Effect of Feeding Rate and Guar Gum Addition] - Tjahja Muhandri; . Subarna; Nurheni Sri Palupi (Jurnal Teknologi dan Industri Pangan, 2013)
The objectives of this research were to (1) investigate the effect of feeding rate on elongation, cooking loss, and microstructure of wet corn noodle properties and (2) investigate the effect of guar gum on elongation, cooking loss, hardness, and sensory quality of wet corn noodle. Corn noodles were made with pasta extruder. Two levels of feeding rate, i.e. 2.10 g/second and 1.87 g/second and three levels of guar gum (0, 1, 2% based on flour weight) were applied during wet corn noodle processing. Increase in feeding rate resulted in increased elongation, decreased cooking loss, and corn noodles microstructure similar to wheat noodle. Addition of guar gum increased elongation, but decreased hardness and cooking loss of the corn noodle. Additionally, guar gum decreased the preference scores.